ACCOUNTING BALANCE (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER'S THEORY, 2024)
This article delves into the evolving significance of balance sheets beyond their traditional role. Through literature review and empirical insights, we explore their dynamic nature and the influence of technology and regulations. From assessing solvency to ESG reporting, balance sheets reflect financial and non-financial performance, guiding strategic decisions. Embracing a holistic approach is crucial for organizations to leverage balance sheets for sustainable growth and stakeholder trust.